State and Trade in the Indonesian Archipelago - Schutte, G.J. (sian Studies - Book Archive pre-2000., 1995)
The theme of this volume, state formation and mercantile evolution in Indonesia, has been the subject of historiographical debate for quite some time. In recent decades the focus of this debate has shifted from the external challenge posed by westerners towards the indigenous response to that challenge and towards local and regional situations, adding to the knowledge of state and state formation. Nine case studies on state formation in the Indonesian archipelago illustrate this approach. They deal with widely differing states, in different periods and regions, ranging from the twelfth-century Javanese state of Kadiri to the twentieth-century Netherlands Indies colonial state, and from Riau and West Borneo to Buton and the Seram Sea. Most of the studies concern states that came under the influence of the Dutch East Indies Company or its successor, the Dutch colonial state. The contributors to this volume are from Indonesia-Muhammad Gade Ismail, R.Z. Leirissa, Edi Sedyawati and Suhartono-and from the Netherlands-F. van Baardewijk, V.J.H. Houben, L.W. Nagtegaal, J.W. Schoorl and R. Vos. Based on in-depth bibliographical and archival research, these studies shed new light on historical situations and processes, thus contributing significantly to the knowledge of Indonesia's past and its historiography.